CBMT-16. EGFRvIII EXPRESSION CONFERS CHEMOSENSITIVITY BY INCREASING DNA MISMATCH REPAIR PROTEIN EXPRESSION AND REPLICATION STRESS. (11th November 2019) - Struve, Nina; Binder, Zev A; Stead, Lucy F; Brend, Tim; Bagley, Stephen J; Faulkner, Claire; Ott, Leonie; Müller-Goebel, Justus; Weik, Anna-Sophie; Hoffer, Konstantin; Rieckmann, Thorsten; Christin Parplys, Ann; et al.
Abstract: MGMT promoter methylation is the only accepted biomarker with prognostic role in GBM but its routine implementation is limited partly response to TMZ is heterogeneous, but also due to lack of effective alternative treatment options. Therefore, additional biomarkers are needed to enable better prediction of survival and to improve individualized treatment of GBM patients. A potential new biomarker is the epidermal growth factor receptor variant III (EGFRvIII). This constitutively activated deletion variant is present in approximately one third of all IDH wildtype GBM, but its relevance to treatment response is poorly understood. The aim of the present study was to analyze the impact of endogenous EGFRvIII expression on chemosensitivity and the mechanisms underlying any differential treatment response. EGFRvIII expression was associated with prolonged median overall survival but only for GBM patients with MGMT promoter methylated tumors. In line with this, we observed increased TMZ sensitivity of EGFRvIII+ and MGMT promoter methylated cells, which translated into improved survival in xenograft experiments. The increased TMZ sensitivity was associated with an elevated DNA damage induction accompanied by an increased expression of DNA mismatch repair (MMR) proteins in EGFRvIII+ cell lines and EGFRvIII+ GBM patient samples. Subsequently, only a moderate reduction in MMR protein expression resulted in a dramatic TMZ resistance, suggesting that EGFRvIII expression specifically sensitized MGMT deficient cells to TMZ treatment by upregulating MMR. Furthermore, EGFRvIII expression in GBM cell lines was accompanied by increased DNA damage, replication fork slowing, stalling and enhanced origin firing, implying replication stress. Targeting of EGFRvIII-dependent replication stress by irinotecan led to hypersensitivity of EGFRvIII+ cells. Taken together this study illustrates that EGFRvIII-induced upregulation of MMR and replication stress increases chemosensitivity thereby highlighting the vulnerability of EGFRvIII+ GBM to available treatments. These important data may also guide the development of new and more effective personalized strategies.